Signals of adaptation to agricultural stress in the genomes of two European bumblebees - Hart, Alex F.; Verbeeck, Jaro; Ariza, Daniel; Cejas, Diego; Ghisbain, Guillaume; Honchar, Hanna; Radchenko, Vladimir G.; Straka, Jakub; Ljubomirov, Toshko; Lecocq, Thomas; Dániel-Ferreira, Juliana; Flaminio, Simone; et al. (Frontiers in Genetics, 2022)
Human-induced environmental impacts on wildlife are widespread, causing major biodiversity losses. One major threat is agricultural intensification, typically characterised by large areas of monoculture, mechanical tillage, and the use of agrochemicals. Intensification leads to the fragmentation and loss of natural habitats, native vegetation, and nesting and breeding sites. Understanding the adaptability of insects to these changing environmental conditions is critical to predicting their survival. Bumblebees, key pollinators of wild and cultivated plants, are used as model species to assess insect adaptation to anthropogenic stressors. We investigated the effects of agricultural pressures on two common European bumblebees, Bombus pascuorum and B. lapidarius. Restriction-site Associated DNA Sequencing was used to identify loci under selective pressure across agricultural-natural gradients over 97 locations in Europe. 191 unique loci in B. pascuorum and 260 in B. lapidarius were identified as under selective pressure, and associated with agricultural stressors. Further investigation suggested several candidate proteins including several neurodevelopment, muscle, and detoxification proteins, but these have yet to be validated. These results provide insights into agriculture as a stressor for bumblebees, and signal for conservation action in light of ongoing anthropogenic changes.